PENGARUH GAYA KEPEMIMPINAN OTOKRATIS DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA PADA KARYAWAN PT MAHADANA ASTA BERJANGKA CABANG KUNINGAN JAKARTA SELATAN - Rahmat Putra Jaya Gulo, Dese; Romdonih, Faisal (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the influence of leadership style and work productivity on work productivity. At PT Mahadana Asta Berjangka, Kuningan Branch, South Jakarta. The population and sample in this research were all employees at PT Mahadana Asta Berjangka, Kuningan Branch, South Jakarta, totaling 90 employees. The research method used is a quantitative method, a data collection method by distributing questionnaires which are processed using regression analysis. The tests used research instruments are validity and reliability. Multiple linear regression, correlation, determination and hypothesis using the t (partial), F(simultaneous) with SPSS 23. The research results for the Leadership Style variable (X1) have a ttest  value of 4.301 while ttable is 1.666 with the regression equation Y=9.915+0.377X1. This means that the Leadership Style variable (X1) has a positive effect on Work Productivity (Y), and significant results were obtained showing a value of 0.000 < 0.05. The Work Discipline variable (X2) has a t value of 3.812 > ttable 1.666 with a regression of Y=9.915+0.391X2. This means that the Work Discipline variable (X2) has a positive effect on Work Productivity (Y), and significant results were obtained showing a sig value of 0.000 < 0.05. The results of simultaneous statistical tests can be concluded that the F value is 36.354 with a significance of 0.000, while the Ftable is 3.10 with multiple linear regression analysis Y=9.915+0.377X1+0.391X2. So use a significant limit of 0.05. The correlation value is 0.675, this shows that there is a strong relationship and the contribution of the independent variable's influence is 46% on Work Productivity (Y) at PT Mahadana Asta Berjangka, Kuningan Branch, South Jakarta.